Pengaruh Debt Covenant Dan Growth Opportunity Terhadap Konservatisme Akuntansi - Muhammad Rivandi (Universitas Negeri Padang, 2019)
Abstract This study aimed to obtain empirical evidence of the effect of debt covenant and growth opportunities on the accounting conservatism. This study considered as quantitatif research. The population in this study is a manufacturing company listed in the Indonesia Stock Exchange in the year 2012-2016. Sampling method used is purposive sampling. The method of analysis used is regresion panel analysis. The results showed that 1) Debt covenant have a significant negative effect on the accounting conservatism. 2) Growth opportunitieshas not have effect on the accounting conservatism. In this study suggested: 1) For the next researchers who are interested in researching the same title should add another variable, because of the model used in this research, it is known that the variables used in this research can explain 60,82%. 2) The period of resource must be lengthen, so that the trend every year can cacth in resource and with the number of a bigger company sample.